Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/jhep11(2012)140
|View full text |Cite
|
Sign up to set email alerts
|

Drastic reduction of cutoff effects in 2-d lattice O(N) models

Abstract: Abstract:We investigate the cutoff effects in 2-d lattice O(N ) models for a variety of lattice actions, and we identify a class of very simple actions for which the lattice artifacts are extremely small. One action agrees with the standard action, except that it constrains neighboring spins to a maximal relative angle δ. We fix δ by demanding that a particular value of the step scaling function agrees with its continuum result already on a rather coarse lattice. Remarkably, the cutoff effects of the entire st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 55 publications
(112 reference statements)
2
28
0
Order By: Relevance
“…In this case, even the leading power of this logarithmic term differs between the standard action and topological actions [28].…”
Section: Critical Value Of the Helicity Modulusmentioning
confidence: 96%
“…In this case, even the leading power of this logarithmic term differs between the standard action and topological actions [28].…”
Section: Critical Value Of the Helicity Modulusmentioning
confidence: 96%
“…The essential features of walking technicolor models are shared by this toy model and can be accurately investigated by numerical simulations. Optimized lattice actions have also been studied intensively in [25] for 2-d O(N ) models, where it has been shown that cut-off effects can be reduced to the per mille level. A topological lattice action has also been used in a recent study of 4-d U (1) gauge theory, to demonstrate that the correct continuum limit is obtained, to examine the effect of the lattice action on monopole condensation in the confined phase, and to test a method to measure the free energy [26].…”
Section: Jhep03(2016)116mentioning
confidence: 99%
“…One of them is used to set the lattice spacing a, the other to estimate the size of the cut-off effects at the given resolution. For the 2-d O(N ) spin model these were [25] the mass gap measured on a long strip with spatial sizes L and 2L (cf. step scaling function, [27]).…”
Section: Determination Of the Parameters Of The Actionmentioning
confidence: 99%
“…In a recent paper [8] a class of models was identified with very small lattice artifacts. Some of these models are particularly fascinating since they seem to belong to the same universality class as the standard-type actions described above but don't have the usual classical limit and so far a perturbative treatment for them is unknown (see subsection 1.2).…”
Section: Contentsmentioning
confidence: 99%